ANALISIS KESALAHAN BERBAHASA PADA TUTURAN PEMBAWA ACARA DAN BINTANG TAMU DALAM TALK SHOW HITAM PUTIH YANG BERJUDUL “FENOMENA KANJENG DIMAS” - Fauziah Nurul Fatimah; Dewi Purnamasari; Desih Pratiwi; Dida Firmansyah (IKIP Siliwangi, 2018)
Language is a tool which is used by human in communication activities. In communication, the language used can be a written aspect or a spoken aspect. In spoken activity, we often find some mistakes in speaking a language. This case is happened because of the limitation about the knowledge of language speaker. This research is aimed to correct the mistakes found in speaking by using language mistakes analysis which is focused on two aspects namely the kind of mistakes aspect and region aspect and the mistake characteristic. The research method which is used in this research is qualitative research. The result showed that a spoken can be analyzed by using language mistake analysis.